2023
DOI: 10.1136/bmjqs-2023-016730
|View full text |Cite
|
Sign up to set email alerts
|

What and when to debrief: a scoping review examining interprofessional clinical debriefing

Julia Paxino,
Rebecca A Szabo,
Stuart Marshall
et al.

Abstract: IntroductionClinical debriefing (CD) improves teamwork and patient care. It is implemented across a range of clinical contexts, but delivery and structure are variable. Furthermore, terminology to describe CD is also inconsistent and often ambiguous. This variability and the lack of clear terminology obstructs understanding and normalisation in practice. This review seeks to examine the contextual factors relating to different CD approaches with the aim to differentiate them to align with the needs of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(229 reference statements)
0
2
0
Order By: Relevance
“…15 This is where the focus of the debrief is on giving participants space to focus on reactions to an event, rather than focusing on the experience itself in detail. Paxino et al's scoping review 9 excluded papers primarily describing psychologically focused debriefings, but noted that some of the included studies 'reported an intersection between quality improvement and supporting the emotional and psychological needs of team members'. Therefore, the aim of a prompted CD may be either to learn, to manage emotional responses or an amalgamation of both.…”
Section: Prompted CD To or Managementioning
confidence: 99%
See 1 more Smart Citation
“…15 This is where the focus of the debrief is on giving participants space to focus on reactions to an event, rather than focusing on the experience itself in detail. Paxino et al's scoping review 9 excluded papers primarily describing psychologically focused debriefings, but noted that some of the included studies 'reported an intersection between quality improvement and supporting the emotional and psychological needs of team members'. Therefore, the aim of a prompted CD may be either to learn, to manage emotional responses or an amalgamation of both.…”
Section: Prompted CD To or Managementioning
confidence: 99%
“…6 Our focus should now be shifting towards overcoming barriers to implementation, a disappointingly difficult feat. 7 8 The paper by Paxino et al 9 in this issue of BMJ Quality & Safety responds to this call and suggests that a lack of standardised terminology to describe CD practices may be part of the implementation problem.…”
mentioning
confidence: 99%